STUDYING THE EFFECTIVENESS OF TREATMENT WITH REMOVABLE PROTESES FOR TOOTH-RELATED ELDERLY PATIENTS - Matrizayeva Gulmira Ne'matjon qizi; Omonova Dilnura Ulugbek qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Relevance of the research. The relevance of this research stems from the urgent demographic shift in Uzbekistan, where 23% of the population will be over 60 by 2030 (WHO 2022), creating unprecedented demand for age-appropriate dental prosthetics. The study specifically addresses critical gaps in Khorezm region, which faces severe healthcare disparities with only 4.2 dentists per 10,000 population compared to the 7.1 national average. This research provides the first comprehensive evaluation of removable prostheses for elderly patients in Central Asia, where evidence-based guidelines are currently lacking. Traditional acrylic prostheses show particularly poor outcomes in geriatric populations, with 37% developing stomatitis due to atrophic mucosal changes and declining manual dexterity compromising hygiene. Our study uniquely examines both clinical outcomes and socioeconomic factors influencing prosthetic success in resource-limited settings. The findings will directly inform national geriatric oral health policies, dental education reforms, and public health resource allocation. By comparing conventional acrylic versus flexible RPDs, we address three fundamental gaps: material efficacy in aging physiology, cost-benefit analysis in low-resource regions, and age-specific treatment modifications. This work aligns with UN Sustainable Development Goal 3 (Good Health) and WHO’s 2023 Oral Health Strategy for Aging Populations, while establishing the first evidence-based framework for prosthetic selection in Central Asian elderly patients. The research outcomes will reduce iatrogenic complications, optimize limited healthcare resources, and improve quality of life for the region’s rapidly growing elderly population facing partial edentulism.